Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538970
|View full text |Cite
|
Sign up to set email alerts
|

Comparing educational experiences and on-the-job needs of educational software designers

Abstract: This paper reports on part of the findings of a mixed-methods study which explored the educational experiences of Computing Professionals who design and develop educational software. A particular focus is given on the gaps professionals perceive between what was covered in their formal (university) education and the skills and knowledge that have been most important to them in their professional roles. Discrepancies were found particularly in areas related to practical skills (such as testing, maintaining code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…As suggested in previous research and confirmed by our results, soft skills such as problem solving, teamwork, communication, and lifelong learning are crucial for graduates to become well-rounded professionals [9][10][11][12]14 . These findings are not surprising.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…As suggested in previous research and confirmed by our results, soft skills such as problem solving, teamwork, communication, and lifelong learning are crucial for graduates to become well-rounded professionals [9][10][11][12]14 . These findings are not surprising.…”
Section: Discussionsupporting
confidence: 74%
“…As discussed in our earlier work [14][15] , habits that may be construed as cheating within a traditional educational environment are considered not only good life-long learning practice, but are essential skills for success on the job by computing professionals, including, but not limited to, asking for help and feedback from mentors and peers; reusing existing code and components were possible; and finding sample design or code in books, online sources, or their own prior work to experimenting with and adapting it to their own use.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Direct observation of developers has confirmed that these skills play a large role in daily work and present substantial challenges [2]. Surveys further have revealed that developers learn many such skills on the job, reflecting gaps between skill upon graduation and respective accumulated skill thereafter [3,4].…”
Section: Introductionmentioning
confidence: 94%